The Political Sustainability of Germany's Environmental Tax Rate - Kerstin Roeder; Wolfgang Habla (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
We analyze the German ecotax package in a model of overlapping generations and majority voting. The package consists of the ecotax rate and the budgetary rule which assigns a fraction of the tax revenue to the reduction of pension contributions while holding pension benefits constant. The old and the young generation have different preferences with respect to the tax rate and the use of the tax revenue. Our theoretical model as well as the calibration of our model show that the median voter s preferred tax rate may well exceed the efficient tax rate whenever his income is sufficiently high. This is the likelier the more CO2 is degraded and removed from the atmosphere. Furthermore, the median voter prefers earmarking of tax revenue to reductions in pension contributions. The latter is quite an accurate prediction of the situation in Germany where the share of tax revenue devoted to the pension scheme amounts to more than 90%.
Keywords: H23; H55; D78; 330